Increased hippocampal CD38 and systemic inflammation after partial hepatectomy does not induce impairment of spatial cognition - Schnitzler, Sebastian; Kopitz, Jürgen; Plaschke, Konstanze (Neurological research, 2016)
The role of inflammation in cognitive alterations in a post-operative setting is still not fully understood. Surgical interventions can cause systemic inflammations which eventually can induce neuroinflammation. However, the main causes of functional changes after surgery are still elusive. In this study, we investigated the role of CD38, a TNFα-inducible NADH+ cyclase and hydrolase. We assume that CD38 overexpression impairs mitochondrial ATP synthesis. Within the hippocampus, the resulting cellular death could lead to cognitive impairment.
Gesehen am 20.05.2020